2016
DOI: 10.5530/jyp.2016.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Transdermal Delivery of Glimepiride Via Entrapment in Proniosomal Gel

Abstract: Objective: The aim of this study is to formulate and evaluate proniosomal gel formulations as transdermal delivery systems of glimepiride (GM) to improve its therapeutic efficacy. Methods: Proniosomal formulations have been prepared using different types of non-ionic surfactants with cholesterol in different molar ratios. Proniosomal gel; PN 16 (Span 60, Tween 60, Cholesterol; 35:35:30 molar ratio) that exhibits maximum EE % (94.01 ± 0.88) and most prolonged release was chosen for ex-vivo skin permeation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Currently, most the active pharmaceutical ingredients suffer from low solubility and bioavailability, which could be avoided via applying nanotechnology in developing drug delivery systems. A number of nanocarriers have been successfully developed, including nanoparticles, nanoemulsion, ethosome, niosome and liposome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most the active pharmaceutical ingredients suffer from low solubility and bioavailability, which could be avoided via applying nanotechnology in developing drug delivery systems. A number of nanocarriers have been successfully developed, including nanoparticles, nanoemulsion, ethosome, niosome and liposome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas for niosomal formulations F TS and F SB it was 2.125 ± 0.44 and 2.375 ± 0.2314 hours respectively. The higher Tmax of niosomal formulations was owing to the slow dissolution and extended release of the drug from niosomes (Abdallah et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The results reveal that formula 11 (tween 60, HLB= 14.9) has the highest EE% (58.43%) while Formula 15 (tween 60and40, HLB= 15.25) has the smallest EE% (9.52 %). These findings could be attributed to the affinity of cholesterol to lipophilic surfactant [16]. The results of in vitro release have shown that formula F1 (HLB= 14.9) has the highest release 97.5% compared to formula F7 (HLB= 15.25) which has the lowest in vitro release 89.1%.…”
Section: Determination Of Ee%mentioning
confidence: 96%